FASCISMS AND HISTORICAL CONSCIOUSNESS: crisis of meaning and political violence - Arouche Costa Leite, Paulo Victor (2022)
The article aims to analyze the concept of fascism, its approaches and the possibility of using the concept to categorize far-right political movements in the contemporary world, highlighting George Orwell's elaborations on fascism from his journalistic and fictional writings. The methodology applied was the literature review from the perspective of analysis of Social History and the History of concepts.